Transformasi Bimbingan dan Konseling dalam Konteks Masyarakat Modern dan Sederhana : Studi Perbandingan - Setyorini, Ragil; F, Firman; N, Nurfahanah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study discusses the comparison between online counseling and face-to-face counseling in handling various psychological and behavioral problems of individuals. The research method used was a review analysis, which aims to explore and compare both counseling approaches through a review of relevant literature and scholarly articles. Data were collected through sources such as Google Scholar and Scopus.com, and systematically analyzed using tables to identify the differences, advantages, and limitations of each method in providing guidance and counseling services. The study also evaluated factors such as accessibility, effectiveness, convenience, as well as the interaction between counselor and client in different social contexts, both in modern and simple societies. Study results showed that online counseling offered easier access, convenience, and flexibility, yet the quality of the working relationship was lower compared to face-to-face counseling. Face-to-face counseling, while limited by logistical and cost constraints, is more effective in building emotional connections and providing more in-depth direct support. This study recommends the integration of both approaches to provide more flexible and effective solutions, as well as assessing the extent to which both can be applied in various social contexts.